2018
DOI: 10.1159/000493490
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of the GPR55 Antagonist, CID16020046

Abstract: Background/Aims: CID16020046 blocks the effect of the lipid lysophosphatidylinositol (LPI) at its receptor, GPR55. CID16020046 and another antagonist, ML193, have been used to investigate GPR55-mediated effects of LPI on cells, tissues, and in vivo. Here we describe the structure-activity relationship of CID16020046. Methods: Yeast or human cells were engineered to express GPR55 or control receptors. Cells were pretreated with a test agent before agonist challenge. Functional responses were quantified by yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In this spotlight, LPI-GPR55 axis inhibitors may be an effective strategy to suppress cancer progression. Moreover, a GPR55 peptide ligand was shown to suppress the proliferation of B-lymphoblastoid cell lines [292].…”
Section: Cancermentioning
confidence: 99%
“…In this spotlight, LPI-GPR55 axis inhibitors may be an effective strategy to suppress cancer progression. Moreover, a GPR55 peptide ligand was shown to suppress the proliferation of B-lymphoblastoid cell lines [292].…”
Section: Cancermentioning
confidence: 99%
“…The pyrazolopyrrolidinone chemotype is well-described in the research and patent literature, with a rich array of reported biological activities, the most prominent of which are p53/MDM2 interaction inhibition (41)(42)(43)(44)(45)(46)(47)(48)(49), phosphodiesterase inhibition (50,51), and GPR55 modulation (52)(53)(54)(55)(56). In addition, there are examples of pyrazolopyrrolidinones exhibiting P2X3 antagonism (57), GPR68 agonism (58), 5-HT1A receptor binding (59), BET inhibition (60, 61), 14-3-3-PMA2 interaction stabilization (62), P-glycoprotein inhibition (63), antitumor activity (64), and antimicrobial activity against various parasitic, viral and bacterial species including T. cruzi (65), HIV (66,67), flaviviruses (68), M. tuberculosis (69, 70), P. falciparum (71,72), and V. cholerae (73).…”
Section: Medicinal Chemistry Of Pyrazolopyrrolidinones Establishing P...mentioning
confidence: 99%
“…Interestingly, data shows that CBD acts as an inverse agonist of GPR55 and, therefore, inhibits the LPI-induced stimulation of ERK1/ 2 phosphorylation (Anavi-Goffer et al, 2012) and the stimulation of [ 35 S]GTPγS binding by LPI (Ford et al, 2010). Research has revealed the structure-activity relationship of GPR55 with the selective antagonist CID16020046, while the antagonism of GPR55 has been proposed as an efficacious treatment for several neurological diseases (Brown et al, 2018). CID16020046 has been used to study the physiological role of GPR55 in nociception (Okine et al, 2020), cognitive processes (Marichal-Cancino et al, 2016;Hurst et al, 2017;Marichal-Cancino et al, 2018), and the neuroprotective effects observed in neuroinflammation and Dravet syndrome animal models (Kaplan et al, 2017;Shen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%